Learning Video in Mathematics Online Learning: Study of the Effectiveness in Improving Learning Outcomes - Siti Nurkhayati; Andi Prastowo (JENIUS (Journal of Education Policy and Elementary Education Issues), 2022)
This research is motivated by students' low mathematics learning outcomes during the Covid-19 pandemic. The purpose of this study was to reveal the effectiveness of using KineMaster Video to improve online mathematics learning outcomes for Madrasah Ibtidaiyah students. The type of research used is a quantitative Quasi Experiment. This research was conducted in the even semester of the 2021/2022 academic year. This research used all MIM Ngadirejo students as the population, while for the sample, it used Class V students. Respondents for the experimental class were 13 students using KineMaster video media, and for the control class, 12 students were using PowerPoint. The research instrument used was multiple choice questions consisting of 10 questions on addition and subtraction of fractions. The first data analysis is a prerequisite test with a normality test and homogeneity test. Further data analysis was carried out by testing the research hypothesis using an independent sample t-test for the pretest scores of both classes and post-test scores for both classes. The results showed that using KineMaster video media improved the learning outcomes of fifth-grade students at MI Muhammadiyah Ngadirejo compared to the control class, which only used power points.